Activation of specific bitter taste receptors by olive oil phenolics and secoiridoids - Meng Cui (Nature Portfolio, 2021)
Abstract Extra-virgin olive oil (EVOO) is a critical component of the Mediterranean diet, which has been found beneficial to human health. Bitterness is often positively associated with the presence of phenolic compounds in EVOO. There are twenty-five bitter taste receptors (TAS2Rs) in humans, each of which responds to specific bitter tastants. The identity of phenolic compounds and the bitter taste receptors they stimulate remain unknown. In this study, we isolated 12 phenolic and secoiridoid compounds from the olive fruit and the oil extracted from it, and tested their ability to stimulate bitter taste receptor activity, using a calcium mobilization functional assay. Our results showed that seven out of twelve studied compounds activated TAS2R8, and five of them activated TAS2R1, TAS2R8, and TAS2R14. The phenolic compounds oleuropein aglycon and ligstroside aglycon were the most potent bitter tastants in olive oil. TAS2R1 and TAS2R8 were the major bitter taste receptors activated most potently by these phenolic compounds. The results obtained here could be utilized to predict and control the bitterness of olive oil based on the concentration of specific bitter phenolics produced during the milling process of olives.